Algebras generated by special symmetric polynomials on _1 - Jawad, F.; Karpenko, H.; Zagorodnyuk, A.V. (Carpathian Mathematical Publications, 2019)
Let X be a weighted direct sum of infinity many copies of complex spaces _1_1. We consider an algebra consisting of polynomials on X which are supersymmetric on each term _1_1. Point evaluation functionals on such algebra gives us a relation of equivalence `' on X. We investigate the quotient set X/ and show that under some conditions, it has a real topological algebra structure.